Trauma culturale tra memoria e comunicazione nell’emergenza pandemica in Italia (Società e diritti, 2023)
The sociology of culture has defined cultural trauma as a condition in which the members of a community feel they have been subjected to a horrible event which has left indelible traces on their group conscience and which has marked their memories forever, changing their future identity in a fundamental and irrevocable way. The catastrophic events linked to the coronavirus pandemic could certainly have produced wounds and scars in the collective fabric. In this essay, we have two distinct but intertwined goals. On the one hand, we want to show the many critical issues that have characterized the communication produced in Italy during the pandemic. On the other hand, we intend to show how this criticality can lead to a widespread cultural trauma. In particular, we intend to show how the latter can arise, at the same time, from a distorted use of public memory and from the production of a memory based on a traumatic catastrophic imaginary.